Optimasi Algoritma SHA-256 dan Metode Salt Untuk Pengamanan Akun Calon Santri Baru Pesantren Almuslim - Syauqa Mardhatillah; Sri Winar; Dedy Armiady (Fakultas Ilmu Komputer Universitas Almuslim, 2025)
This is due to the various techniques used by unauthorized parties to gain access to account information. Therefore, protecting passwords must be a top priority, including in the management of prospective student accounts at Almuslim Islamic boarding school. This study aims to design and implement a login system for online student registration by securing user accounts using the SHA-256 hashing algorithm combined with the salt method. The security process is carried out by hashing the password after adding a unique salt, ensuring that the stored data is not in plain text. The results of testing show that the system is able to securely store account data and successfully verify users during login through hash and salt matching